2005
DOI: 10.1007/s00428-005-0127-8
|View full text |Cite
|
Sign up to set email alerts
|

Misalignment of pulmonary vessels with alveolar capillary dysplasia: association with atrioventricular septal defect and quadricuspid pulmonary valve

Abstract: Misalignment of pulmonary vessels (MPV) with alveolar capillary dysplasia (ACD) is a complex congenital vascular abnormality in newborn infants. This condition is often associated with persistent pulmonary hypertension, which leads to severe respiratory distress and finally to the death of the newborn. Here, two cases of MPV with ACD are reported that were associated with atrioventricular septal defects. Both cases showed a combination of a large atrial septal defect and a smaller subvalvular ventricular septa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 12 publications
0
5
0
1
Order By: Relevance
“…2004; Roth et al. 2006; Bagci et al. 2009), cardiomyopathy has not been previously reported in this disorder.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2004; Roth et al. 2006; Bagci et al. 2009), cardiomyopathy has not been previously reported in this disorder.…”
Section: Resultsmentioning
confidence: 99%
“…This case was confirmed to have trisomy X by karyotyping. Although congenital structural heart defects are known to be in the clinical spectrum of trisomy X (Haverty et al 2004;Roth et al 2006;Bagci et al 2009), cardiomyopathy has not been previously reported in this disorder. Therefore, whether trisomy X contributes to the cardiomyopathy in this patient is uncertain.…”
Section: Whole Gene Duplicationsmentioning
confidence: 95%
“…Another disorder more prevalent in infancy is alveolar capillary dysplasia (ACD), which is a rare fatal developmental disorder that results in severe persistent pulmonary hypertension of the newborn typically in the first days of life . Commonly diagnosed at autopsy, the presence of ACD has been documented in several case series and a large number of case reports . There have also been small case series and/or case reports of pulmonary hypertension in several other specific chILD entities, none of which qualified for inclusion in our review, but include pulmonary hypoplasia, capillary hemangiomatosis, pulmonary interstitial glycogenosis, pulmonary hemosiderosis, Lymphocytic interstitial pneumonia, Langerhans cell histiocytosis, and pulmonary vasculitis with hyperesinophilia …”
Section: Discussionmentioning
confidence: 99%
“…In about 10%, alveolar capillary dysplasia is associated with congenital heart disease. 1,[3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] The clinical picture is dominated by progressive cyanosis in an infant with signs of respiratory distress because of severe neonatal pulmonary arterial hypertension. The outcome is always fatal even if prolonged survival for several months has been reported.…”
Section: A Lveolar Capillary Dysplasia Is a Congenitalmentioning
confidence: 99%